Physical processes in electron devices: Analysis of the radio pulse forming in the overdimensional resonator with the interference-type switch; Journal of Communications Technology and Electronics; Vol. 42, № 8 - Artemenko S. N. Sergey Nikolaevich; Avgustinovich V. A. Vladimir Andreevich; Kaminsky V. L. Valery Ludvigovich; Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich (1997, 1997)
В фонде НТБ ТПУ отсутствует